The Effect of Temperature in Enhancing Antagonism Ability for Penicillium Carneum Against Some Damping Off Pathogens - Zghair, Fadhil Sami (International Journal of Psychosocial Rehabilitation, 2020)
Biological control one of the important methods against plant pathogens. Damping off disease one of the risk soil born fungal disease caused by Pythium aphanidermatum and Fusarium solani. This study aim to isolation and identification of the bioagent penicillium carneum in dual culture with under range of temperature culture plate method. also evaluated cold and heated crud filtrated against two pathogen invetro. The results showed that Penicillium carneum had highly antagonsitic activity against Pythium aphanidermatum and Fusarium solani, 35ºC showed the favorable temperature for strong antagonism. and the lower temperature caused reduction Penicillium carneum antagonistic activity. the 25% cool crud concentration caused reduction in radial growth of two pathogen in 81.1% and 64.2% for Pythium aphanidermatum and Fusarium solani respectively, while heated crud caused growth reduction 57.7%, 45.7% for two pathogens respectively.